2014
DOI: 10.1016/j.jtcvs.2013.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of systemic to pulmonary artery shunts in patients weighing less than 3 kg: Analysis of shunt type, size, and surgical approach

Abstract: In this high-risk group of neonates weighing less than 3 kg at the time of SPS, survival to discharge and the next planned surgical procedure was high. Outcomes were good with the 3.5- and 4-mm shunts; however, shunt reintervention was common with 3-mm shunts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 23 publications
4
43
1
4
Order By: Relevance
“…Low weight has persistently been demonstrated as a risk factor for mortality after the Norwood operation, including in recent series from experienced institutions [11,12,14]. Similarly, low weight has been associated with increased mortality risk after BTS due to shunt occlusion related to the small sized shunts or systemic steal due to excessive pulmonary blood flow that is likely more common in smaller babies [16,17]. In a recent review of the Society of Thoracic Surgeons database, weight less than 3 kg at surgery was an independent risk factor for hospital mortality after BTS [16].…”
Section: Commentmentioning
confidence: 98%
“…Low weight has persistently been demonstrated as a risk factor for mortality after the Norwood operation, including in recent series from experienced institutions [11,12,14]. Similarly, low weight has been associated with increased mortality risk after BTS due to shunt occlusion related to the small sized shunts or systemic steal due to excessive pulmonary blood flow that is likely more common in smaller babies [16,17]. In a recent review of the Society of Thoracic Surgeons database, weight less than 3 kg at surgery was an independent risk factor for hospital mortality after BTS [16].…”
Section: Commentmentioning
confidence: 98%
“…First-stage palliation of neonates born with SV and associated restricted pulmonary blood flow is one of the major indications for mBTS in the current era [1][2][3][4][5][6]. A recent report examining The Society of Thoracic Surgeons (STS) database showed that 62% of mBTS performed in the US were actually for cardiac anomalies that were amenable for eventual biventricular repair [2].…”
Section: Commentmentioning
confidence: 99%
“…We were unable to identify risk factors for shunt revision in our series. A recent report from Milwaukee [3] showed that shunt reintervention was required in 17% of neonates after mBTS and identified shunt size 3.0 mm and extracardiac malformations as risk factors for reintervention. Another report, from Philadelphia [7], showed that shunt intervention was required in 9.7% of neonates after mBTS and identified heterotaxy syndrome, extracardiac malformations, and lower weight as risk factors for reintervention.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations